The Supraorbital Approach for Recurrent or Residual Suprasellar Tumors - McLaughlin, N.; Ditzel Filho, L.F. S.; Shahlaie, K.; Solari, D.; Kassam, A. B.; Kelly, D. F. (min - Minimally Invasive Neurosurgery, 2011)
Suprasellar tumors can be removed through a variety of approaches including conventional frontotemporal craniotomies, the transsphenoidal route, or the supraorbital (SO) eyebrow craniotomy. Herein we assess the utility of the SO route for recurrent or residual suprasellar tumors previously treated by an alternative route.A retrospective analysis of all consecutive patients who underwent an SO approach for removal of a recurrent/residual tumor was undertaken.Between December 2007 and February 2010, 11 patients underwent an SO craniotomy for a recurrent or growing residual tuberculum sellae meningioma (n=7) or craniopharyngioma (n=4). All 11 patients had prior craniotomies, 5 had transsphenoidal surgery, 6 had radiation treatment, and 1 had chemotherapy. In the last 5 cases, the endoscope was used in addition to the microscope for intraoperative visualization. 3 patients underwent decompression of multicystic craniopharyngiomas and the remaining 8 patients had tumor debulking, all achieving 70% or more tumor removal. Of 9 patients with preoperative visual deterioration, 6 (67%) had improvement and no patient had visual worsening. No new adenohypophysis or neurohypophysis dysfunction was noted. One patient had a postoperative CSF leak requiring reoperation.The SO approach should be considered as a safe and effective alternative route for recurrent or residual suprasellar tumors previously treated by conventional craniotomy or TS surgery. It typically offers a simplified trajectory that minimizes scar tissue from prior approaches and provides excellent access for optic apparatus decompression. Endoscopy is helpful to visualize hidden tumor remnants and maximize safe tumor removal.
Keywords: supraorbital approach; transsphenoidal surgery; endoscope; meningioma; craniopharyngioma; tumor recurrence